2021
DOI: 10.1182/blood.2020007782
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease quantification in ovarian tissue collected from patients in complete remission of acute leukemia

Abstract: Ovarian tissue cryopreservation (OTC) is offered to women treated for acute leukemia to preserve their fertility before hematopoietic stem cell transplantation. The risk of leukemic infiltration in ovarian samples harvested before administration of chemotherapy limits ovarian tissue transplantations. We assessed the minimal residual disease (MRD) by sensitive quantitative polymerase chain reaction in cryopreserved ovarian cortex and medulla samples harvested from 30 patients in complete remission of acute leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…However, molecular analysis could be performed just before autotransplantation of ovarian cortex to con rm MFC results, as was done in patient 2, for example. The ndings presented in this study are congruent with previous reports from other teams [34,35,38,40].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, molecular analysis could be performed just before autotransplantation of ovarian cortex to con rm MFC results, as was done in patient 2, for example. The ndings presented in this study are congruent with previous reports from other teams [34,35,38,40].…”
Section: Discussionsupporting
confidence: 93%
“…MRD evaluation in the residual medulla, when available, is recommended by ESHRE [22]. In our study, MRD results for the cortex and medulla were concordant in 3 patients, and in line with a recent study where 20/24 MRD results were concordant [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, studies have shown that OTC retrieved after the patient has achieved complete remission in the bone marrow in most cases also is negative for leukemia markers in the cryopreserved ovarian tissue (8,13,14) and OTCs that scored negative for molecular leukemic markers did not transfer leukemia to the recipient mice (13). In a recent study Chevillon and coworkers investigated the presence of minimal residual disease (MRD) in OTC harvested from acute leukemia patients that achieved complete remission and showed significant concordance between bone marrow and OT; however, 4/9 discordant patients had undetectable MRD in the bone marrow while positive in the OT (15).…”
Section: Case Reportmentioning
confidence: 99%
“… 13 In a recent study Chevillon and co-workers investigated the presence of minimal residual disease (MRD) in OTC harvested from acute leukemia patients that achieved complete remission and showed significant concordance between bone marrow and OT; however, four of nine discordant patients had undetectable MRD in the bone marrow while positive in the OT. 15 …”
mentioning
confidence: 99%